2018
DOI: 10.1653/024.101.0105
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Protein as Food Baits forAnastrepha obliqua(Diptera: Tephritidae): Tests in a Wind Tunnel and the Field

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
5
0
4
Order By: Relevance
“…A eficiência do monitoramento da população de moscas-das-frutas depende da localização, tipo de armadilha e variedade das frutas (Mesquita et al, 2018). Por exemplo, para a manga, a população, diversidade e frequência das espécies de moscasdas-frutas varia em relação à região, temporada e variedade de manga cultivada (Soares et al, 2020).…”
Section: Contextualização E Análiseunclassified
See 1 more Smart Citation
“…A eficiência do monitoramento da população de moscas-das-frutas depende da localização, tipo de armadilha e variedade das frutas (Mesquita et al, 2018). Por exemplo, para a manga, a população, diversidade e frequência das espécies de moscasdas-frutas varia em relação à região, temporada e variedade de manga cultivada (Soares et al, 2020).…”
Section: Contextualização E Análiseunclassified
“…A isca mosca é um atrativo proteico indicado para monitoramento de mosca-das-frutas em pomares comerciais, normalmente utilizado em conjunto com a armadilha "BOLA". A proteína de hidrolisado de milho se mostrou atrativo em túnel de vento, entretanto no campo não foi atrativa, apenas o Bionis YE MF® puro e o Bionis YE MF® com açúcar foram atrativos para A. obliqua (Mesquita et al, 2018).…”
Section: Contextualização E Análiseunclassified
“…We found that apple cider vinegar-based bait can't attract like BSG because this exported apple cider vinegar from china contain less protein source. In the insecticide-bait sprays programme, the mixture of yeast extract and sucrose is a good attractant for Anastrepha oblique but only sucrose is not effective in the experiment [16].…”
Section: Discussionmentioning
confidence: 99%
“…Os parasitoides são produzidos a partir de pupários de moscas-das-frutas e para tal, é necessário que indivíduos de mosca-das-frutas sejam capturados dos seus hospedeiros (Adaime et al, 2017;. O parasitismo pode ser influenciado pelas características dos frutos, tal como, tamanho, cor, odor, espessura de polpa e estágio de maturação (Mesquita et al, 2018;Araújo et al, 2020). Soares et al (2020) verificou que a população, diversidade e frequência das espécies das moscas-das-frutas variava de acordo com a região, temporada e variedade dos frutos de manga cultivados.…”
Section: Culturas Estudadasunclassified